Characterization of Exopolysaccharides from Lactiplantibacillus plantarum PC715 and Their Antibiofilm Activity Against Hafnia alvei - Xiqian Tan; Bingyu Ma; Xiaoqing Wang; Fangchao Cui; Xuepeng Li; Jianrong Li (Microorganisms)
Exopolysaccharides (EPSs) secreted by lactic acid bacteria have the potential to enhance human health by showing various biological functions. This study investigated the biological role and antibiofilm properties of EPS715, a new neutral EPS produced by pickled vegetables originating from Lactobacillus plantarum PC715. The results indicate that EPS715 is primarily composed of rhamnose, glucose, and mannose. Its molecular weight (Mw) is 47.87 kDa, containing an α-glucoside linkage and an α-pyranose ring. It showed an amorphous morphology without a triple helix structure. Furthermore, EPS715 showed improved antioxidant activity. Specifically, its scavenging capacity of ABTS+ radicals, DPPH radicals, and the hydroxyl (·OH) reduction capacity at 5 mg/mL was 98.64 ± 2.70%, 97.37 ± 0.79%, and 1.64 ± 0.05%, respectively. Its maximal scavenging capacity was >40%, and the hydroxyl (·OH) radical scavenging ability was dose-dependent. Moreover, the biofilm of various pathogens including S. aureus, B. cereus, S. saprophyticus, Acinetobacter spp., and H. alvei was substantially dispersed and affected by EPS715, with a maximum inhibition rate of 78.17% for H. alvei. The possible mechanism by which EPS715 shows antibiofilm properties against the H. alvei may be attributed to its effects on the auto-aggregation, hydrophilic characteristics, and motility of Hafnia spp. Thus, EPS715 has significant antioxidant and antibiofilm characteristics that may hold substantial potential for applications in food and medicinal products.